Political socialization, parental separation, and political ideology in adulthood - van Ditmars, Mathilde M.; Bernardi, Fabrizio (Frontiers in Political Science, 2023)
The increase in divorce rates over the past decades challenges the traditional image of the two-parent family, as new family forms are increasingly more common. Yet, the traditional view of the family has remained central to political socialization research. Therefore, we propose and empirically test a theoretical framework regarding the consequences of parental separation for processes of political socialization. While the impact of parental divorce has been studied extensively by sociologists, the political implications of this impactful life event have remained largely uncovered. We identify two mechanisms that we expect to predict more leftist political orientations in children of separated parents compared to those from intact families: experiences of economic deprivation and single-mother socialization. Multi-level analyses using the European Values Study (2008) and two-generational analyses with the Swiss Household Panel (1999–2020) support our expectations, indicating that in case of parental separation offspring tends to hold more leftist political orientations, controlling for selection into parental separation and the intergenerational transmission of political ideology. We find empirical support for mechanisms of economic deprivation and single-mother socialization across our analyses. The implications of our findings are that in the family political socialization process, offspring's political orientations are not only influenced by their parents' ideology, but also by formative experiences that result from the family structure.